Al-Maqrīzī's al-Ḫabar ʿan al-bašar : Vol. V, Section 6: The Greeks, the Romans, the Byzantines, the Franks, and the Goths - Penelas, Mayte, (Bibliotheca Maqriziana ;, 2020)
This volume contains the edition and translation of the chapter of al-Maqrīzī's al-Ḫabar ʿan al-bašar dealing with Greeks, Romans, Byzantines, Franks, and Goths. This chapter is, for the most part, an almost exact reproduction of Ibn Ḫaldūn's Kitāb al-ʿIbar , from which al-Maqrīzī derived material from many other sources, including prominent Christian sources such as Kitāb Hurūšiyūš , Ibn al-ʿAmīd's History , and works by Muslim historians like Ibn al-Aṯīr's Kāmil. Therefore, this chapter of al-Ḫabar ʿan al-bašar is a continuation of the previous Arabic historiographical tradition, in which European history is integrated into world history through the combination of Christian and Islamic sources.